Dehumanization of Teaching and Learning Activities on Social Science Subject - Nafiati, Dewi Amaliah (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
This research aims to describe factors that influence dehumanization of teaching and learning processes. The population of this research was 158 students. The research used a proportional cluster random sampling and 40 students were analyzed as samples. Data were collected by using documentation, observation and questionnaire. The data then quantitatively and qualitatively classified due to the influence of teaching and learning factors on Social Science subject in order to draw the conclusion easily. Findings show that the influence of dehumanization factors on teaching and learning processes are teaching method by 77.9%, curriculum factor by 85%, teacher-student relationship by 63.7%, school discipline by 75.4%, homework by 65.4%, school time by 63.7%, learning equipment by 70.8%, over-standard lesson by 81% and building condition by 80%. The most dominant factor influencing the dehumanization of teaching and learning processes is curriculum by 85%. Thus, teachers are required to improve their competences and capabilities to create a more humanistic teaching learning processes which are more appropriate to the goals of education. In order to achieve the goals, it is recommended to the school administrators to improve the facilities and infrastructure for more conducive teaching and learning processes with more representative spaces and facilities.